A case of iatrogenic severe mitral regurgitation - D’Aloia, Antonio; Piovanelli, Barbara; Rovetta, Riccardo; Bonadei, Ivano; Vizzardi, Enrico; Curnis, Antonio; Metra, Marco (Monaldi Archives for Chest Disease, 2015)
Bromocriptine and cabergoline, ergot derived dopamine receptor agonists used to treat Parkinson’s disease and prolactinomas, have been associated with increased risk of cardiac valve disease. Here we present a case of iatrogenic symptomatic severe mitral regurgitation due to these drugs.